2020
DOI: 10.1097/md.0000000000023094
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of adverse pregnancy outcome for pre-pregnancy couples in Hunan, China

Abstract: To identify the prevalence of chronic disease and behavior risk factors of adverse pregnancy outcome for pre-pregnancy couples in Hunan province, China. A retrospective study including cross-sectional datas from the Free Pre-pregnancy Health Check (FPHC) surveillance system of Hunan, China in 2019 was conducted. Microsoft Excel 2010 was used for preliminary data analysis. The fowllowing descriptive analysis, t-tests, and Chi-Squared tests were carried out using SPSS 25.0. Among 419,971 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Only 42 neonates with low birth weight were delivered in our study and there was no significant difference between the two groups. After adjustment using multivariable logistic regression, older age, especially older than 35 years, was also seen as an important risk factor of adverse pregnant outcomes, which is similar to the results of a previous study (22). There are some limitations in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Only 42 neonates with low birth weight were delivered in our study and there was no significant difference between the two groups. After adjustment using multivariable logistic regression, older age, especially older than 35 years, was also seen as an important risk factor of adverse pregnant outcomes, which is similar to the results of a previous study (22). There are some limitations in our study.…”
Section: Discussionsupporting
confidence: 85%
“…The most pronounced decreases in trends in ASR of prevalence, DALYs and death were observed for maternal hemorrhage. The declined trends might be due to the general economic growth, a reduced fertility rate [3] , and the Free Pre-pregnancy Health Check (FPHC) surveillance program initiated by the Health Ministry of China in 2010 [16] . Besides, for reducing the maternal mortality, China initiated the national Five Strategies for Maternal and Newborn Safety (FSMNS), which is composed of five parts: (1) pregnancy risk screening and assessment strategy, (2) case- by- case management strategy for high- risk pregnancies, (3) referral and treatment strategy for critically ill pregnant women and newborns, (4) reporting strategy for maternal deaths (and 5) accountability strategy [17] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] On the other hand, the prevalence rate in China is about 56 per 1000 live births. [ 2 ] Previously, we have reported that a total of 17753 in 925413 surveilled perinatal infants suffer BDs between 2005 and 2014 in Hunan province, China. [ 3 ] Our further study showed that the heredity and advanced maternal age (>35 years) are the major factors bringing BDs, and the other factors, including drinking, radiation, smoking, etc, also lead to BDs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Our further study showed that the heredity and advanced maternal age (>35 years) are the major factors bringing BDs, and the other factors, including drinking, radiation, smoking, etc, also lead to BDs. [ 2 ] Except those factors, medication use during pregnancy is an important and complicated factor involved in BD occurrence. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation